73.0k views
2 votes
Solve for u.
4(u-3)-6=-4(-6u+6)-4u​

2 Answers

5 votes

Answer:

3/8 (Fraction form)

Step-by-step explanation:

Let's solve your equation step-by-step.

4(u−3)−6=−4(−6u+6)−4u

Step 1: Simplify both sides of the equation.

4(u−3)−6=−4(−6u+6)−4u

(4)(u)+(4)(−3)+−6=(−4)(−6u)+(−4)(6)+−4u(Distribute)

4u+−12+−6=24u+−24+−4u

(4u)+(−12+−6)=(24u+−4u)+(−24)(Combine Like Terms)

4u+−18=20u+−24

4u−18=20u−24

Step 2: Subtract 20u from both sides.

4u−18−20u=20u−24−20u

−16u−18=−24

Step 3: Add 18 to both sides.

−16u−18+18=−24+18

−16u=−6

Step 4: Divide both sides by -16.

−16u

−16

=

−6

−16

User Kurt Mueller
by
5.8k points
6 votes
The answer is


3/8=0.375
User Viacheslav Ivanov
by
5.5k points